Religion in the Roman Empire - Berthelot, Katell (Religion in the Roman empire, 2025)
"Religion in the Roman Empire" (RRE) aims to advance and document new and integrative perspectives on religion in the ancient world, combining multidisciplinary methodologies. Committed to interdisciplinarity and new approaches to the study of religion, it offers a space to take up recent, but still incipient, research to modify and cross the disciplinary boundaries of the History of Religion, Archaeology, Anthropology, Classics, Ancient History, Jewish History, Rabbinics, New Testament, Early Christianity, Patristics, Coptic Studies, Gnostic and Manichean Studies, Late Antiquity and Oriental Languages. We hope to stimulate the development of new approaches that can encompass the local and global trajectories of the multi-dimensional pluralistic religions of antiquity.